Pengaruh Kualitas Pelayanan Terhadap Kinerja Pengurus Koperasi Unit Desa (KUD) Sari Usaha Tani Desa Kota Baru Kabupaten Rokan Hulu - Krisfandi, Dana (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
The researchers' goal is to do research, 1.mengetahui impact of service quality on the performance board Village Unit Cooperatives (KUD) Sari Village Farms New Town Rokan Hulu, 2. Determine the influence of service quality on board performance Village Unit Cooperatives (KUD) Sari Village Farms New Town Rokan Hulu. Subjects in this study is a member of the Village Unit Cooperatives (KUD) Sari Village Farms New Town Rokan Hulu for 87 orang.Teknis collecting data in this study using the method of data collection methods of observation, interviews, and questionnaires. Data analysis technique consists of quantitative analysis and descriptive analysis. This research was done by testing a few instruments such as Test Validity and reliability test. Results of testing the hypothesis with the t test obtained significant value that the value of Sig. <0.05, which means a significant difference between the quality of service to performance management Village Unit Cooperatives (KUD) Sari Village Farms New Town Rokan Hulu, 2. The amount of influence the quality performance management service to the Village Unit Cooperatives (KUD) Sari Village Farms New Town Rokan Hulu, can be seen in the value of 88.7% keofisien determination that could be construed that the variable Kualita Services (X) has the effect of a contribution of 88.7% to performance variable (Y) and the remaining 11.3% is influenced by other variables outside of the variable X or studied. The researchers suggest cooperative management of Sari village farms need to improve service and performance in order to maintain royalitas and satisfaction of the members of the cooperative and the need to evaluate an organization can go forward in the future